Penerapan Kualitas dan Kemasan Pada Usaha Kerupuk di Desa Lumpatan Sekayu - Omar Hendro; Wani Fitriah; Belliwati Kosim (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The application of quality and packaging to the cracker business in Lumpatan Sekayu Village is the title or topic of the Community Service Team. Providing counseling in the field of marketing management that specializes in quality and packaging of crackers. The implementation of this community service is by means of direct counseling to the cracker business owner and their workers. The goal is that cracker-making businesses can increase their production as a result of increased sales. The quality and packaging of the crackers has not been the concern of this cracker business maker. Several findings by the Community Service Team concluded in the report, 1). so far they have not considered the quality and packaging of the crackers. 2). The use of traditional means of production and drying, cracker size is not standard. 3). Do not have a business, health and halal permit from the relevant government agency. 4). The local government still lacks attention to cracker entrepreneurs, which are a household industry involving the workforce of local housewives. The Community Service Team after providing counseling will monitor and guide, so that these cracker processors carry it out. The team will provide a way out or a solution if they find a problem. The ultimate goal of community service is to improve the welfare of the owner and maker of crackers as well as the community in Lumpatan Sekayu Village.